Persepsi, Pengetahuan dan Sikap Komunitas Masyarakat dalam Pengendalian Penularan di Era Covid-19 - Salma Merda Kawati; Dewi Elizadiani Suza; Amira Permatasari Tarigan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This systematic review aims to assess public perceptions, knowledge and attitudes in controlling transmission in the Covid-19 era. The method used is a systematic review by searching articles from the Proquest, Pubmed and EBSCO databases selected using the PRISMA diagram. The research results show that public perception of the Covid-19 pandemic is positive, public knowledge of Covid-19 and public attitudes in controlling the risk of transmission are good. Some people have followed all recommendations such as following lockdown guidelines and taking precautions such as washing hands frequently, using masks when leaving the house, maintaining distance and doing work from home. In conclusion, public perception of Covid-19 is positive, and public knowledge about Covid-19 and public attitudes in controlling the risk of transmission are good. Keywords: Covid-19, Society, Perception, Knowledge, Attitude